42.3k views
0 votes
Show all work to solve by factoring 3x^2 − x − 2 = 0.

User Jeff Maes
by
6.0k points

1 Answer

6 votes

Answer:

The solutions are x=1 and x=-2/3

Explanation:

we have


3x^(2)-x-2=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


3x^(2)-x=2

Factor the leading coefficient


3(x^(2)-(1/3)x)=2

Complete the square. Remember to balance the equation by adding the same constants to each side


3(x^(2)-(1/3)x+(1/36))=2+(1/12)


3(x^(2)-(1/3)x+(1/36))=25/12

Rewrite as perfect squares


3(x-(1/6))^(2)=25/12


(x-(1/6))^(2)=25/36

square root both sides


(x-(1/6))=(+/-)(5/6)


x=(1/6)(+/-)(5/6)


x=(1/6)(+)(5/6)=1


x=(1/6)(-)(5/6)=-2/3

User Zedenem
by
6.1k points